Analisis Kesesuaian Persyaratan Puskesmas Kelurahan di Provinsi Dki Jakarta dengan Peraturan Menteri Kesehatan Nomor 43 Tahun 2019 tentang Puskesmas - Aris Nurzamzami; Dumilah Ayuningtyas (Syntax Corporation, 2023)
The purpose of this study is to analyze in depth the suitability in terms of quantity and quality of Village Puskesmas with 7 requirements in Permenkes Number 43 of 2019 concerning Puskesmas. This research was conducted with a qualitative-interpretative approach by utilizing secondary data, namely Facility Research. Health in 2019, Indonesia Health Profile in 2020 and DKI Jakarta Provincial Health Profile in 2020. The secondary data taken by the researcher was then analyzed, compared and concluded to see the suitability of the Village Health Center with Permenkes 43 of 2019 concerning Puskesmas. The results of the study showed that the suitability of Village Puskesmas in DKI Jakarta Province to the 7 Requirements of the Minister of Health 43 of 2019, only pharmaceutical requirements have reached 100% or all Puskesmas, while the requirements for location, buildings, infrastructure, equipment, personnel and clinical laboratories have not reached 100%. The conclusion is that the Village Puskesmas in DKI Jakarta province in quantity has been fulfilled but the quality of the Village Puskesmas according to the requirements of Permenkes 43 still has shortcomings. Recommendations for policy changes to the DKI Jakarta Provincial Government in the form of Revisions to Governor Regulation 386 of 2016 concerning the Structure and Organization of Puskesmas in DKI Jakarta Province which are considered irrelevant today. In the Revision of the Governor's Decree on Puskesmas must be synchronized with regulations at the national level, and added with the addition of clauses on health services in DKI Jakarta Province that better reach the community to the level of community harmony or neighborly harmony